الألفاظ العربية في اللغة التركية الحديثة دراسة صوتية معجمية - عيساني، حنين, عبيد، رانية (Univerity of Eloued, 2022)
من المعلوم أن اللغة العربية أثرت في لغات بعض الشعوب بصفة عامة وعلى اللغة التركية بشكل خاص, ومن هذا المنطلق دخلت على اللغة التركية كلمات كثيرة من اللغة العربية ، وخضعت هذه الأخيرة للنظام الصوتي التركي , ومن ثم تغير نطق الكثير منها في اللغة التركية. ومن خلال دراستنا التحليلية التفصيلية التطبيقية لهذا الموضوع خلصنا إلى أن : *عدد الصوامت في اللغة العربية ثمانية وعشرون وفي اللغة التركية واحد وعشرون صامتا , في حين عدد الصوائت في اللغة العربية ثلاثة ويقابلها في اللغة التركية ثمانية صوائت . *و تجدر بنا الإشارة إلى أن صفات الأصوات الموجودة في اللغة العربية لا توجد في اللغة التركية. *كما لاحظنا التباين والاتفاق من حيث اللفظ و المعنى بين اللغتين. It is known that the Arabic language affected other languages in general and the Turkish language in particular, From this point, many words from the Arabic language entered the Turkish language, and the latter was subject to the Turkish phonetic system, and then the pronunciation of many of them changed in the Turkish language. Through our detailed applied analytical study of this topic, we concluded that: The number of consonants in Arabic language is 28 while in Turkish language is 21, however, the number of vowels in Arabic language is 3 and corresponds to 8 in Turkish language. It should be noted that the characteristics of sounds in Arabic language are not found in the Turkish language, we also noted the contrast and agreement in terms of pronunciation and meaning among the two languages. On one hand, there are words that have similar meaning and differ in pronunciation; on the other hand, we have noticed that there are words that differ in meaning and have similar pronunciation and the scale by which we measured the Turkish lexicon and the Arabic lexicon, as well as our writing the phonetic writing of the two languages represent the best evidence for that.
Keywords: الأصوات ، اللفظ ، المعنى ، اللغة التركية; Sounds, pronunciation, meaning, Turkish language